ANALISIS KESIAPAN IMPLEMENTASI REKAM MEDIS ELEKTRNIK DITINJAU DARI SUMBER DAYA MANUSIA DAN SARANA DAN PRASARANA DI RUMAH SAKIT UMUM DAERAH Dr. DARSONO KABUPATEN PACITAN PROVINSI JAWA TIMUR - Wartini (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2023)
Technological developments have made the medical record paradigm develop from traditional paper to digital/electronic, and the implementation of PMK Number 24 of 2022 concerning medical record in 2023. Implementation of medical record services at RS Dr. Darsono, Pacitan Regency, the obstacles that are often encountered are delays in sending outpatient medical records, errors in collection and storage, increasingly limited storage space for medical records as the number of patients increases, ambiguity in filling out medical records so that it is possible for misinterpretation to occur among users of the record data. medical. This research aims to determine the readiness to implement electronic medical records from the human resources and infrastructure aspects. This research design uses descriptive research methods with a qualitative approach. The research sample is RME users consisting of doctors, nurses, medical records officers, and IT personnel. The sampling technique is purposive sampling. The research instrument uses an interview guide. Data analysis methods include data reduction, data presentation, and conclusion. The research results from human resources and infrastructure aspects are quite ready to implement RME. In the HR aspect of the service, officers are available, in IT, programmers are still needed to develop the RME system and HR needs to receive training. In terms of infrastructure, both infrastructure and financial aspects are available to support the implementation of RME, but there needs to be additional facilities to support the smooth running of RME. Dr Darsono Hospital needs to carry out a needs analysis to prepare for the implementation of RME and compatible infrastructure and competent human resources to support the implementation of RME. Keywords: Electronic medical records, human resources, infrastructure